1999
DOI: 10.1074/jbc.274.47.33609
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosoma cruzi Contains Major Pyrophosphate Stores, and Its Growth in Vitro and in Vivo Is Blocked by Pyrophosphate Analogs

Abstract: High field31 P nuclear magnetic resonance spectroscopy showed that inorganic pyrophosphate (P 2 O 7 4؊ ) is more abundant than ATP in Trypanosoma cruzi, the causative agents of Chagas' disease. These results were confirmed by specific analytical assays, which showed that in epimastigotes, the concentrations of inorganic pyrophosphate and ATP were 194.7 ؎ 25.9 and 37.6 ؎ 5.5 nmol/mg of protein, respectively, and for the amastigote form, the corresponding concentrations were 358.0 ؎ 17.0 and 36.0 ؎ 1.9 nmol/mg o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
144
0
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 148 publications
(152 citation statements)
references
References 55 publications
6
144
0
2
Order By: Relevance
“…(Fig. 1), determined by electron probe X-ray microanalysis, showed the presence of acidocalcisome-like organelles which have been reported to be rich in these elements [31][32][33][34][35][36][37][38]. This assumption was supported by the finding that the parasites displayed a vacuolar H + -PPase localized in organelles of same size and distribution (Fig.…”
Section: Discussionsupporting
confidence: 74%
“…(Fig. 1), determined by electron probe X-ray microanalysis, showed the presence of acidocalcisome-like organelles which have been reported to be rich in these elements [31][32][33][34][35][36][37][38]. This assumption was supported by the finding that the parasites displayed a vacuolar H + -PPase localized in organelles of same size and distribution (Fig.…”
Section: Discussionsupporting
confidence: 74%
“…PHO80 forms a complex with its CDK partner PHO85 and phosphorylates the transcription factor PHO4 in response to changes in phosphate concentration in the cell (42,55). Recently it has been shown that pyrophosphate is a major store of inorganic phosphate and is more abundant than ATP in trypanosomes (56). The pyrophosphate is located in part in an unusual organelle, the acidocalsisome (57,58).…”
Section: Discussionmentioning
confidence: 99%
“…Several bisphosphonates are potent inhibitors of bone resorption and are in clinical use for the treatment and prevention of osteoporosis, Paget disease, hypercalcemia caused by malignancy, tumor metastases in bone, and other diseases (13). In early work, it was shown that nitrogen-containing bisphosphonates were effective in the inhibition of T. cruzi, in vitro and in vivo, without toxicity to the host cell (14). More recently, we tested a series of bisphosphonates for their effects on the growth of T. gondii, T. brucei rhodesiense, Leishmania donovani, and Plasmodium falciparum in vitro, finding that several bisphosphonates can effectively inhibit the growth of these parasites (15).…”
mentioning
confidence: 99%